Non-aqueous electrolyte and lithium ion battery

By using bis(trimethylsilyl)lithium phosphate and heptafluorobutyryl imidazole as additives in lithium-ion batteries, the formation of phosphate-rich interface film and low-polar separator is solved by overcharge and low-temperature environments of lithium-ion batteries. The performance problems improve the battery's overcharge and cycle performance and reduce safety risks.

CN119230936AActive Publication Date: 2024-12-31SHENZHEN HIGHPOWER TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411342929.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The problem of destruction of the structure of the positive electrode material during overcharging and deterioration of cycling performance in low-temperature environments, especially the safety risks and performance degradation caused by transition metal dissolution and increased electrolyte viscosity.

Method used

Using a non-aqueous electrolyte containing bis(trimethylsilyl) lithium phosphate and heptafluorobutyryl imidazole as additives, the conduction rate of lithium ions and the separator are improved by forming a phosphate-rich interface film and a low-polar separator. Wetting properties reduce free electrolyte, inhibit dissolution of positive electrode metal ions, and take into account the infiltration and overcharge resistance of electrolyte.

Benefits of technology

It effectively improves the anti-overcharge performance and low-temperature cycling performance of lithium-ion batteries, reduces battery thickness, reduces safety risks, and improves the overall performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

In order to solve the problems that in the prior art, a positive electrode of a lithium ion battery is damaged in an overcharge environment, and cycle performance is deteriorated under a low-temperature condition, the non-aqueous electrolyte and the lithium ion battery are provided, the non-aqueous electrolyte comprises additives, an organic solvent and lithium salt, and the additives comprise bis (trimethylsilyl) lithium phosphate and heptafluorobutyrylimidazole; the non-aqueous electrolyte satisfies the following conditions: 0.5 < = A < = 3, and 0.5 < = B < = 3; wherein A% is the mass percentage content of bis (trimethylsilyl) lithium phosphate in the non-aqueous electrolyte; and B% is the mass percentage of heptafluorobutyryl imidazole in the non-aqueous electrolyte. The non-aqueous electrolyte provided by the invention meets the following conditions: when A is more than or equal to 0.5 and less than or equal to 3, and B is more than or equal to 0.5 and less than or equal to 3, the synergistic effect of bis (trimethylsilyl) lithium phosphate and heptafluorobutyrylimidazole can be effectively exerted when bis (trimethylsilyl) lithium phosphate and heptafluorobutyrylimidazole are combined, and the infiltration and overcharge resistance of the electrolyte are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The invention belongs to the technical field of chemical energy storage devices, and in particular relates to a non-aqueous electrolyte and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in consumer electronics and power batteries due to their high specific energy, fast charging and discharging capabilities, and low self-discharge. However, when lithium-ion batteries are overcharged, transition metals (cobalt, nickel, iron, manganese, etc.) in the positive electrode material are easily dissolved, causing structural damage to the positive electrode material. At the same time, oxygen is released and reacts violently with the electrolyte, which can easily cause safety accidents when the battery is overcharged. In low-temperature environments, the electrolyte has a poor wetting effect due to increased viscosity, which can easily deteriorate the performance of the battery in low-temperature cycles.

[0003] Usually, the low-temperature cycle performance of the battery can be improved by increasing the wettability and increasing the liquid retention of the battery cell. However, traditional wetting agents such as fluorobenzene are easily decomposed under high voltage, and increasing the liquid retention will increase the overall thickness of the battery cell, affecting the appearance of the battery and reducing the volume energy density of the battery. In order to solve the above technical problems, it is urgent to develop a new type of lithium-ion electrolyte. Summary of the invention

[0004] Aiming at the problems in the prior art that the positive electrode of lithium-ion batteries is damaged in an overcharge environment and the cycle performance deteriorates under low temperature conditions, a non-aqueous electrolyte and a lithium-ion battery are provided.

[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a non-aqueous electrolyte comprising an additive, an organic solvent and a lithium salt, wherein the additive comprises lithium bis(trimethylsilyl)phosphate and heptafluorobutyrylimidazole; The non-aqueous electrolyte meets the following conditions: 0.5≤A≤3, 0.5≤B≤3; Wherein, A% is the mass percentage of lithium bis(trimethylsilyl)phosphate in the non-aqueous electrolyte; B% is the mass percentage of heptafluorobutyrylimidazole in the non-aqueous electrolyte.

[0006] Optionally, the non-aqueous electrolyte satisfies the following conditions: 0.33≤A / B≤3.

[0007] Optionally, the non-aqueous electrolyte satisfies the following conditions: 0.38≤B / X; Here, Xg / Ah is the liquid retention capacity of the non-aqueous electrolyte.

[0008] Optionally, the liquid retention volume of the non-aqueous electrolyte is 1.1≤X≤2.5.

[0009] Optionally, based on the mass of the electrolyte being 100%, the mass percentage of the organic solvent is 55% to 85%.

[0010] Optionally, based on the mass of the electrolyte being 100%, the mass percentage of the lithium salt is 8% to 16%.

[0011] Optionally, the organic solvent includes one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, methyl acetate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0012] In another aspect, the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and the non-aqueous electrolyte.

[0013] Optionally, the positive electrode includes a positive electrode active material layer and a positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes lithium iron phosphate, lithium manganese iron phosphate and LiNi x Co y Mn (1-x-y) M z O2, (0.3≤x≤0.9, x+y<1, 0≤z<0.08, M is Al, Mg, Zr Ti) materials or more.

[0014] Optionally, the negative electrode includes a negative electrode active material layer and a negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes natural graphite, artificial graphite, mesophase microcarbon balls, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or more.

[0015] The beneficial effects of the present invention are: The non-aqueous electrolyte provided by the present invention includes an additive, bis(trimethylsilyl) lithium phosphate, which helps to form a phosphate-rich interface film on the surface of the negative electrode. This type of interface film helps to improve the conductivity of lithium ions. In addition, the trimethylsilyl functional group in the bis(trimethylsilyl) lithium phosphate reacts with acidic substances such as HF and POF3 generated by the non-aqueous electrolyte under high voltage, thereby achieving the effect of removing high-voltage by-products and improving the overcharge resistance of the battery; in addition, the low-polarity perfluorocarbon chain in the heptafluorobutyrylimidazole additive in the non-aqueous electrolyte has good affinity with the non-polar diaphragm, can increase the wettability of the diaphragm, promote Li+ to pass through the diaphragm and evenly deposit on the surface of the negative electrode, thereby effectively improving the battery The invention discloses a novel non-aqueous electrolyte having a low temperature performance and can reduce free electrolyte and battery thickness. The imidazole group in the heptafluorobutyryl imidazole additive can effectively remove trace amounts of H2O and HF in the electrolyte and inhibit the dissolution of positive electrode metal ions, thereby improving the battery's anti-overcharge performance. Since the impedance of the imidazole group forming a film on the negative electrode surface is relatively high, the low temperature performance will be deteriorated, and the phosphate-rich interface film formed by lithium bis(trimethylsilyl) phosphate can effectively compensate for the above problems. The inventors have found through research that the non-aqueous electrolyte meets the following conditions: when 0.5≤A≤3 and 0.5≤B≤3, the combination of lithium bis(trimethylsilyl) phosphate and heptafluorobutyryl imidazole can effectively exert the synergistic effect of the two, taking into account both the infiltration of the electrolyte and the anti-overcharge performance. DETAILED DESCRIPTION

[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0017] The present invention provides a non-aqueous electrolyte, comprising an additive, an organic solvent and a lithium salt, wherein the additive comprises lithium bis(trimethylsilyl)phosphate and heptafluorobutyrylimidazole; The non-aqueous electrolyte meets the following conditions: 0.5≤A≤3, 0.5≤B≤3; Wherein, A% is the mass percentage of lithium bis(trimethylsilyl)phosphate in the non-aqueous electrolyte; B% is the mass percentage of heptafluorobutyrylimidazole in the non-aqueous electrolyte.

[0018] The non-aqueous electrolyte provided by the present invention includes an additive, bis(trimethylsilyl) lithium phosphate, which helps to form a phosphate-rich interface film on the surface of the negative electrode. This type of interface film helps to improve the conductivity of lithium ions. In addition, the trimethylsilyl functional group in the bis(trimethylsilyl) lithium phosphate reacts with acidic substances such as HF and POF3 generated by the non-aqueous electrolyte under high voltage, thereby achieving the effect of removing high-voltage by-products and improving the overcharge resistance of the battery; in addition, the low-polarity perfluorocarbon chain in the heptafluorobutyrylimidazole additive in the non-aqueous electrolyte has good affinity with the non-polar diaphragm, can increase the wettability of the diaphragm, promote Li+ to pass through the diaphragm and evenly deposit on the surface of the negative electrode, thereby effectively improving the battery The invention can improve the low temperature performance of the battery, reduce the free electrolyte and reduce the thickness of the battery, and the imidazole group in the heptafluorobutyryl imidazole additive can effectively remove trace amounts of H2O and HF in the electrolyte, inhibit the dissolution of positive electrode metal ions, and thus improve the battery's anti-overcharge performance; since the impedance of the imidazole group forming a film on the negative electrode surface is relatively high, it will deteriorate the low temperature performance, and the phosphate-rich interface film formed by lithium bis(trimethylsilyl) phosphate can effectively compensate for the above problems. The inventors have found through research that the non-aqueous electrolyte meets the following conditions: when 0.5≤A≤3 and 0.5≤B≤3, the combination of lithium bis(trimethylsilyl) phosphate and heptafluorobutyryl imidazole can effectively exert the synergistic effect of the two, taking into account the electrolyte's wetting and anti-overcharge performance.

[0019] Specifically, the lithium bis(trimethylsilyl) phosphate (LiTMSP) helps to form a phosphate-rich interfacial film on the surface of the negative electrode, which helps to improve the conduction rate of lithium ions in the battery. The improvement effect is more significant than that of traditional film-forming additives such as vinyl sulfate (DTD) and lithium difluorophosphate (LiPO2F2) that reduce interfacial impedance. In addition, the trimethylsilyl (TMS) functional group in the lithium bis(trimethylsilyl) phosphate additive reacts with acidic substances such as HF and POF3 generated by the non-aqueous electrolyte at high voltage (4.9 V), thereby removing high-voltage byproducts, thereby improving the battery's anti-overcharge performance.

[0020] Specifically, the mass percentage of the bis(trimethylsilyl) lithium phosphate may be 0.5%, 0.6%, 0.8%, 1.0%, 1.5%, 1.7%, 2.0%, 2.3%, 2.5% or 3.0%.

[0021] Specifically, the additive heptafluorobutyrylimidazole (HFBMZ) has the advantages of two derivatives. On the one hand, its low-polar perfluorocarbon chain (-CF2CF2CF3) has good affinity with the non-polar diaphragm (polypropylene), which can increase the wettability of the diaphragm, promote Li+ to pass through the diaphragm and be uniformly deposited on the negative electrode surface, thereby effectively improving the low-temperature performance of the battery, and can also reduce the free electrolyte and reduce the battery thickness. On the other hand, the imidazole group in heptafluorobutyrylimidazole can effectively remove trace amounts of H2O and HF in the electrolyte, inhibit the dissolution of positive electrode metal ions, and thus improve the battery's anti-overcharge performance; in addition, since the impedance of the imidazole group forming a film on the negative electrode surface is relatively high, it will deteriorate the low-temperature performance of the battery. At this time, the phosphate-rich interface film formed by the additive lithium bis(trimethylsilyl) phosphate can effectively compensate for the deterioration of the low-temperature performance of the battery caused by the high-impedance interface film formed by the imidazole group.

[0022] Specifically, the mass percentage of the heptafluorobutyrylimidazole can be 0.5%, 0.6%, 0.8%, 1.0%, 1.5%, 1.7%, 2.0%, 2.3%, 2.5% or 3.0%.

[0023] In some embodiments, the non-aqueous electrolyte satisfies the following conditions: 0.33≤A / B≤3.

[0024] In some embodiments, the non-aqueous electrolyte satisfies the following conditions: 0.38≤B / X; Here, X g / Ah is the liquid retention capacity of the non-aqueous electrolyte.

[0025] Specifically, when the liquid retention amount of the heptafluorobutyrylimidazole and the non-aqueous electrolyte satisfies 0.38≤B / X, when the absolute content of the non-aqueous electrolyte is increased, the contact between the non-aqueous electrolyte and the active material can be increased, thereby improving the low-temperature cycle performance of the battery. In addition, the imidazole group of the heptafluorobutyrylimidazole can effectively capture the byproducts of the overcharge condition when the non-aqueous electrolyte content increases, thereby improving the overcharge performance.

[0026] Specifically, Xg / Ah is the liquid retention capacity of the non-aqueous electrolyte, and the liquid retention capacity refers to the amount of electrolyte actually retained inside the battery.

[0027] In some embodiments, the liquid retention capacity of the non-aqueous electrolyte is 1.1≤X≤2.5.

[0028] It should be noted that when the battery is at low temperature, the viscosity of the electrolyte increases, and the electrolyte does not fully infiltrate the battery cell diaphragm, pole piece, etc., which leads to insufficient contact between the electrolyte and the pole piece active material, and thus the battery cycle performance is deteriorated under low temperature conditions. When the absolute liquid retention of the battery is increased, the contact opportunity between the electrolyte and the pole piece and the diaphragm can be increased, which can improve the battery cycle performance at low temperatures. However, when the liquid retention is increased, if the electrolyte is not fully infiltrated on the diaphragm and pole piece, a large amount of electrolyte will be free around the battery shell, causing the battery to swell in appearance, increasing the overall thickness of the battery, thereby reducing the overall volume energy density of the battery, affecting terminal installation, and at the same time, the increase in the battery liquid retention will increase the battery safety risk, because too much electrolyte will also lead to aggravated side reactions and deteriorate the battery safety performance.

[0029] Specifically, in the present application, through a large number of preliminary studies, it was found that when the liquid retention amount of the non-aqueous electrolyte is limited to the range of 1.1≤X≤2.5, the heptafluorobutyrylimidazole and the liquid retention amount can be controlled to maintain a relatively suitable ratio, which is beneficial to promoting the low-temperature cycle performance of the battery.

[0030] Specifically, the liquid retention amount of the non-aqueous electrolyte can be 1.1g / Ah, 1.2g / Ah, 1.3g / Ah, 1.4g / Ah, 1.5g / Ah, 1.6g / Ah, 1.7g / Ah, 2.0g / Ah, 2.1g / Ah, 2.2g / Ah, 2.3g / Ah, 2.4g / Ah or 2.5g / Ah.

[0031] In some embodiments, based on the mass of the electrolyte being 100%, the mass percentage of the organic solvent is 55% to 85%; specifically, the mass percentage of the organic solvent may be 55%, 60%, 65%, 70%, 75%, 80% or 85%.

[0032] In some embodiments, the organic solvent includes one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, methyl acetate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0033] Specifically, in a preferred embodiment, the organic solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (EP) and diethyl carbonate (DEC).

[0034] In some embodiments, based on the mass of the electrolyte being 100%, the mass percentage of the lithium salt is 8% to 16%.

[0035] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium difluorophosphate; in a preferred embodiment, the lithium salt is selected from lithium hexafluorophosphate (LiPF6).

[0036] Another embodiment of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and the non-aqueous electrolyte.

[0037] The lithium-ion battery also includes a diaphragm, which is arranged between the positive electrode and the negative electrode to prevent short circuit problems caused by direct contact between the positive and negative electrodes; specifically, the diaphragm can be a porous sheet or non-woven fabric with excellent liquid retention, and can be a resin or glass fiber diaphragm. The material of the resin or glass fiber diaphragm includes but is not limited to polyolefin, aromatic polyamide, polytetrafluoroethylene, and polyether sulfone.

[0038] The lithium-ion battery also includes a battery shell, which is used to accommodate the electrode assembly composed of the above-mentioned positive electrode and negative electrode core membrane and the electrolyte. Specifically, the battery shell includes but is not limited to a hard shell or a soft shell. When the battery shell is a hard shell, it can be a hard plastic shell, an aluminum shell or a steel shell. When the battery shell is a soft shell, it can be a soft bag, such as a bag-type soft bag. The material of the soft bag can be a plastic material such as polypropylene, polybutylene terephthalate and polybutylene succinate. In addition, the present invention has no special restrictions on the shape of the lithium-ion battery, which can be cylindrical, square or any other shape.

[0039] In some embodiments, the positive electrode includes a positive electrode active material layer and a positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes lithium iron phosphate, lithium manganese iron phosphate and LiNi x Co y Mn (1-x-y) M z O2, (0.3≤x≤0.9, x+y<1, 0≤z<0.08, M is Al, Mg, Zr Ti) materials or more.

[0040] Specifically, the positive electrode active material layer also includes a positive electrode binder and a positive electrode conductor. After the positive electrode binder, the positive electrode conductor and the positive electrode active material are blended, the positive electrode active material slurry is obtained. The positive electrode active material slurry is coated on the positive electrode collector to form a positive electrode active material layer. There is no special restriction on the positive electrode collector. The positive electrode collector can be one of metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper.

[0041] Specifically, the positive electrode binder is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; the positive electrode conductor is selected from at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.

[0042] Specifically, the positive electrode active material slurry is coated on at least one side of the positive electrode current collector.

[0043] In some embodiments, the negative electrode includes a negative electrode active material layer and a negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or more.

[0044] Specifically, the negative electrode active material layer also includes a negative electrode binder and a negative electrode conductor. After the negative electrode binder, the negative electrode conductor and the negative electrode active material are mixed, the negative electrode active material slurry is obtained. The negative electrode active material slurry is coated on the negative electrode collector to form a negative electrode active material layer. There is no special restriction on the negative electrode collector. The negative electrode collector can be one of copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite collector.

[0045] Specifically, the negative electrode binder is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; the negative electrode conductor is selected from at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene. Specifically, the negative electrode binder is the same as or different from the positive electrode binder, and the negative electrode conductor is the same as or different from the positive electrode conductor.

[0046] Specifically, the negative electrode active material slurry is coated on at least one side of the negative electrode current collector.

[0047] The present invention is further described below by way of examples.

[0048] Table 1 Example 1 This embodiment is used to illustrate a non-aqueous electrolyte and a lithium-ion battery disclosed in the present invention, and includes the following operating steps: Preparation of positive electrode The positive electrode active material lithium cobalt oxide, the conductive agent acetylene black (SuperP) and the polyvinylidene fluoride (PVDF) binder are mixed evenly in a mass ratio of 97:1.5:1.5, and evenly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the positive electrode sheet.

[0049] Preparation of negative electrode The negative electrode active material graphite, the conductive agent acetylene black (Super P), the thickener CMC and the binder SBR are mixed evenly in a mass ratio of 94:2:1.2:2.8, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the negative electrode sheet.

[0050] Preparation of electrolyte a. Ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (EP) and diethyl carbonate (DEC) were mixed and stirred in a mass ratio of 10:20:40:30 to form a mixed solvent, water was removed by molecular sieves to obtain an organic solvent for standby use, 1M LiPF6 was added and mixed evenly to obtain a mixture A; b. Add additives to the mixture A obtained in step a, wherein the types and specific amounts of the additives are shown in Table 1, to obtain the electrolyte.

[0051] Battery production The prepared positive electrode sheet, separator and negative electrode sheet are stacked in order so that the separator is located between the positive and negative electrode sheets, and the bare battery cell is obtained by winding and welding the tabs. The bare battery cell is encapsulated in an aluminum-plastic film to obtain a battery.

[0052] Embodiments 2 to 23 Examples 2 to 23 are used to illustrate a non-aqueous electrolyte and a lithium-ion battery disclosed in the present invention, and include most of the operations in Example 1, except that: The types of additives, the amounts of additives, and the relationship between the additives and the liquid retention amount shown in Examples 2 to 23 in Table 1 were used.

[0053] Comparative Examples 1 to 13 Comparative Examples 1 to 13 are used to compare and illustrate a non-aqueous electrolyte and a lithium ion battery disclosed in the present invention, including most of the operations in Example 1, except that: The types of additives, the amounts of additives, and the relationship between the additives and the liquid retention amount shown in Comparative Examples 1 to 13 in Table 1 were used.

[0054] Performance Testing The following performance tests were performed on Examples 1 to 23 and Comparative Examples 1 to 13 prepared as above: Battery performance test: 0℃ cycle test: The test method is: in a constant temperature box at 0±2℃, charge the lithium-ion battery to 4.5V at 1C constant current and constant voltage, cut off the current at 0.05C, and then discharge it to 3V at 1C. Perform multiple charge and discharge cycles under the above conditions, and calculate the capacity retention rate of the battery after 600 cycles, with 5 batteries in each group.

[0055] Capacity retention rate (%) = discharge capacity corresponding to the number of cycles (mAh) / discharge capacity of the third cycle (mAh) * 100% The average value of the capacity retention rate of each group of 5 batteries after different cycles is recorded in Table 1.

[0056] Overcharge test: The test method is: in a constant temperature box at 25±2℃, the lithium-ion battery is continuously charged at a constant current of 1C to 12V, without setting a cut-off current. The battery passes the test if it does not catch fire or explode.

[0057] The passing rate of each group of 20 batteries is recorded in Table 2.

[0058] Table 2 It can be seen from the test results in Table 1 that the test results of Examples 1 to 23 are all better than those of the comparative examples; wherein the additive described in the present application is not added in Comparative Example 1, and the LiTMSP and HFBMZ described in Comparative Examples 2 to 3 are not added at the same time. The obtained test results show that compared with Comparative Example 1, when LiTMSP and HFBMZ are not added at the same time, the 0°C cycle performance and overcharge resistance of the battery cannot be improved. Only when the two are added at the same time can the 0°C cycle performance and overcharge resistance of the battery be significantly improved; according to Comparative Examples 4 and Comparative Examples 10 to 13, compared with the traditional film-forming additives and wetting agents for reducing interfacial impedance, The advantages of LiTMSP and HFBMZ are more obvious when used together. This is because LiPO2F2 (lithium difluorophosphate) and vinyl sulfate (DTD) are traditional film-forming additives for reducing interfacial impedance, and their improvement in the conduction rate of lithium ions is relatively poor compared to the additives described in this application. Fluorobenzene additives are not resistant to high pressure, and imidazole additives have large impedance. Therefore, the above test results show that the combination of LiTMSP and HFBMZ can play a synergistic role and improve the low-temperature cycle performance and overcharge resistance performance; compared with Examples 1 to 7, when the content of LiTMSP and HFBMZ is too high, the low-temperature cycle performance of the battery deteriorates. This is because when the additive content is too high, the electrolyte viscosity rises sharply, which will significantly deteriorate the battery rate performance. When the content of LiTMSP and HFBMZ increases within a certain content range, the low-temperature cycle performance and overcharge resistance of the battery are improved; it can be concluded from the data of Comparative Examples 5 to 7 and Examples 1 to 7 that when 0.5≤A≤3 and 0.5≤B≤3, the additive cost and the comprehensive performance of the battery can be better balanced; according to Examples It can be seen from the test results of Examples 1 to 11 that when the relative HFBMZ content of LiTMSP is too high, it is impossible to effectively take into account the electrolyte wetting and anti-overcharge performance. When the relative content is too low, it is impossible to improve the negative impact of the high impedance of the imidazole group at the interface. Therefore, when 0.33≤A / B≤3, and 0.5≤A≤3 and 0.5≤B≤3 are satisfied, the synergistic effect of the two can be better exerted; According to the test results of Examples 12 to 17, when HFBMZ and the liquid retention amount are maintained at a certain ratio and the battery liquid retention is improved, the battery low temperature The cycle performance can be significantly improved, and the anti-overcharge performance has no significant deterioration. This is because the increase in the absolute content of the electrolyte can increase the contact between the electrolyte and the active material of the electrode, and the imidazole group of HFBMZ can effectively capture the overcharge byproducts produced by the increase in the electrolyte content, thereby improving the overcharge performance. According to the test results of Examples 18 to 23, when the HFBMZ is too low relative to the solution retention, the electrolyte diaphragm infiltration is poor, and too much electrolyte is in a free state, which will greatly increase the thickness of the battery and affect the product appearance and volume energy density of the battery.When HFBMZ is too low relative to the liquid retention amount, increasing the liquid retention amount of the non-aqueous electrolyte will significantly deteriorate the thermal shock performance, and the battery cycle performance is not significantly improved. According to the above data, when 0.38≤B / X is satisfied, HFBMZ can simultaneously improve the battery wetting and anti-overcharge performance; in summary, when the additives lithium bis(trimethylsilyl) phosphate and heptafluorobutyrylimidazole are used in combination in the non-aqueous electrolyte provided by the present invention, the synergistic effect of the two can be effectively exerted; and the liquid retention amount of the heptafluorobutyrylimidazole and the non-aqueous electrolyte meets the following conditions: when 0.38≤B / X, when the absolute content of the non-aqueous electrolyte is increased, the contact between the non-aqueous electrolyte and the active material can be increased, and the low-temperature cycle performance of the battery can be improved. In addition, the imidazole group of the heptafluorobutyrylimidazole can effectively capture the byproducts of the overcharge condition when the non-aqueous electrolyte content increases, thereby improving the overcharge performance.

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A non-aqueous electrolyte, characterized in that: The invention comprises an additive, an organic solvent and a lithium salt, wherein the additive comprises lithium bis(trimethylsilyl)phosphate and heptafluorobutyrylimidazole; The non-aqueous electrolyte meets the following conditions: 0.5≤A≤3, 0.5≤B≤3; Wherein, A% is the mass percentage of lithium bis(trimethylsilyl)phosphate in the non-aqueous electrolyte; B% is the mass percentage of heptafluorobutyrylimidazole in the non-aqueous electrolyte.

2. A non-aqueous electrolyte according to claim 1, characterized in that: The non-aqueous electrolyte meets the following conditions: 0.33≤A / B≤3.

3. A non-aqueous electrolyte according to claim 1, characterized in that: The non-aqueous electrolyte meets the following conditions: 0.38≤B / X; Here, X g / Ah is the liquid retention capacity of the non-aqueous electrolyte.

4. A non-aqueous electrolyte according to claim 1, characterized in that: The liquid retention volume of the non-aqueous electrolyte is 1.1≤X≤2.

5.

5. The non-aqueous electrolyte according to claim 1, characterized in that: Taking the mass of the electrolyte as 100%, the mass percentage of the organic solvent is 55% to 85%.

6. A non-aqueous electrolyte according to claim 1, characterized in that: Taking the mass of the electrolyte as 100%, the mass percentage of the lithium salt is 8% to 16%.

7. The non-aqueous electrolyte according to claim 1, characterized in that: The organic solvent includes one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, methyl acetate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

8. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the non-aqueous electrolyte according to any one of claims 1 to 7.

9. A lithium ion battery according to claim 8, characterized in that: The positive electrode comprises a positive electrode active material layer and a positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises lithium iron phosphate, lithium manganese iron phosphate and LiNi x Co y Mn (1-x-y) M z One or more of the O2 materials; the LiNi x Co y Mn (1-x-y) M z In O2: 0.3≤x≤0.9, x+y<1, 0≤z<0.08, M is Al, Mg, Zr Ti.

10. A lithium ion battery according to claim 8, characterized in that: The negative electrode comprises a negative electrode active material layer and a negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises natural graphite, artificial graphite, intermediate phase micro carbon spheres, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or more.

Citation Information

Patent Citations

  • Electrolyte containing novel additive for lithium ion battery and lithium ion battery

    CN110931865A

  • High-voltage electrolyte adaptive to rapidly-chargeable lithium cobalt oxide battery and application of high-voltage electrolyte

    CN113889667A

  • Non-aqueous electrolyte solution and secondary battery

    CN116779974A

  • Additive for non-aqueous secondary battery, non-aqueous electrolyte for non-aqueous secondary battery, electrode for non-aqueous secondary battery and non-aqueous secondary battery

    JP2023035933A

  • Secondary-battery electrolyte and preparation method therefor, secondary battery, and electronic device

    WO2023072084A1